Manajemen Amil Profesional di Lembaga Amil Zakat Dana Peduli Ummat Kalimantan Timur - Akhmad Nur Zaroni; Norvadewi Norvadewi (Al-Tijary, 2020)
This study aims to determine and analyze the implementation of amil management in LAZ Dana Peduli Ummat (DPU) East Kalimantan. The research was conducted using qualitative methods, by conducting in-depth interviews with Amil LAZ DPU Kaltim in Samarinda, Kutai Kartanegara, and Balikpapan. The data validity was performed using the triangulation method, and data analysis used the Miles and Huberman model. The results showed that the application of amil management in LAZ DPU East Kalimantan were; In the recruitment of amil, HR planning is carried out and the determination of amil's criteria. The work agreement applies the signing of the integrity fact. For the coaching and development of amil, 3 months of training are held for new amil, SDB program (Greetings DPU Blessings) every morning in the early hours of work, CURGAS (Talk of Ideas), Fiqh Zakat School, Training both inside and outside. For performance assessment using KPI (Key Performance Indicator) instrument which is audited internally and externally. While the compensation given is in the form of basic salary, food allowance, health, family, transportation and bonuses. To strengthen Human Resources, four basic principles are applied, namely: the Abdullah and Khalifah principles, justice, organizational goals and individual goals of human resources, and references to the character of the Prophet Muhammad: shiddiq, amanah, fathanah and tabligh. Apart from that, Amil's coaching is also based on values; kafa'ah, amanah and himmatul 'amal.